A prospective study to evaluate neonatal trigger score as an early warning system in post-natal wards - N., Girish; Kalla, Pavankumar S.; S. B., Manjunath; Nisha, Rahumath (International Journal of Contemporary Pediatrics, 2022)
Background: The early postnatal period is a critical phase in newborns as major changes occur in this period. Hence, this study was done to determine the utility of Whitt neonatal trigger score (W-NTS) as a clinical tool. Methods: A prospective observational study was conducted at Kempegowda institute of medical sciences (KIMS) during the period of December 2019 to June 2021. All neonates admitted in postnatal wards of KIMS hospital during the study period were included. Detailed history was taken and NTS observation and scoring chart was applied. Results: NTS chart was applied on a total of 750 neonates who fulfilled the inclusion criteria. Out of 750 neonates, 136 (18.1%) triggered the NTS chart. Twenty-one (15.4%%) neonates did not require any medical intervention while 115 (84.6%) required intervention (25 in post-natal wards (PNW) and 90 in neonatal intensive care unit (NICU). In our study, NTS score of 2 has 78.89% sensitivity and 97.27% specificity for admission to NICU while specificity (100%) was high in NTS score of ≥3. The area under the ROC curve for the NTS was 0.99 with confidence interval of 0.98-0.999 and standard error of 0.005 which was statistically significant. Conclusions: Results from this study shows that W-NTS observation chart acts well as an adjunct to clinical assessment in the PNW, with its simplicity allowing for the successful and safe use.